Hindsight Bias in Expert Surveys: How Democratic Crises Influence Retrospective Evaluations - Olavarria-Gambi, M (SAGE Publications Inc., 2020)
Expert surveys provide a standardized way to access and synthesize specialized knowledge, thereby, enabling the analysis of a diverse range of concepts and contexts that might otherwise be difficult to approach systematically. However, while studies of public opinion have long argued that cognitive biases represent potential problems when it comes to the general population, less attention has been paid to similar issues among expert respondents. This study examines one form of cognitive bias, hindsight bias. Hindsight bias refers to the tendency to retrospectively exaggerate one’s foresight of a particular event. We argue that hindsight bias is a potential problem when it comes to retrospective evaluation due to the difficulty involved in separating our assessments of the pre-crisis period from the knowledge that a crisis occurred. Using disaggregated data from the Varieties of Democracy Project, we look for evidence of hindsight bias in coders’ evaluations of the periods that preceded major crises of democracy. We find that coder disagreement is significantly higher in pre-crisis scenarios than in our control group. Concerningly, despite this disagreement, coders remain similarly confident in their assessments. This represents a potential problem for those who seek to use these data to study democratic breakdowns and transitions. © The Author(s) 2020.